Interference of the Zika Virus E-Protein With the Membrane Attack Complex of the Complement System - Malekshahi, Zahra; Schiela, Britta; Bernklau, Sarah; Banki, Zoltan; Würzner, Reinhard; Stoiber, Heribert (Frontiers in Immunology, 2020)
The complement system has developed different strategies to clear infections by several effector mechanisms, such as opsonization, which supports phagocytosis, attracting immune cells, by C3 and C5 spilt products or direct killing of pathogens by the formation of the membrane attack complex (MAC). As Zika Virus (ZIKV) activates the classical pathway of complement and thus has to avoid clearance by the complement system, we analyzed putative viral escape mechanisms, which limit virolysis. We identified binding of the recombinant viral envelope E protein to components of the terminal pathway of complement (C5bC6, C8 and C9) by ELISA. Western blot analyses revealed that ZIKV E protein interfered with the polymerization of C9, induced on cellular surfaces, either by purified terminal complement proteins or by NHS as a source of complement. Further, hemolytic activity of NHS was significantly reduced in the presence of recombinant E protein or entire viral particles. These data indicate that of ZIKV reduces MAC formation and complement-mediated lysis through binding of terminal complement proteins to the viral E protein.